Agile Development of an Integrated Hajj and Umrah Services Platform: A Case Study of Raudhoh Wisata Bahari - Hapsi Dian Resmihadi; Dendy K Pramudito; Aji Anggono (Jurnal Informatika Ekonomi Bisnis, 2026)
The growth of Hajj and Umrah pilgrimage services in Indonesia demands travel agencies to improve service quality through information technology. Many agencies still manage reservation, payment, and pilgrim data manually, causing service delays, recording errors, and lack of transaction transparency. This study designed and built a web-based Hajj and Umrah reservation and tour management system integrated with Midtrans payment gateway, using the Scrum development methodology. The system supports pilgrim registration, travel package selection, pilgrim data management, and online payment. Black box testing was applied to verify all functional requirements. Results show the system successfully automated reservation and payment confirmation, reducing processing time from 30–60 minutes to 5–10 minutes, improving data accuracy and operational transparency for PT Raudhoh Wisata Bahari.